The Strategies In Overcoming Unregistered Marriages (Nikah Siri) At The Office Of Religious Affairs In Kecamatan Kota Terante Utara Based On Islamic Law Perspective - Muhammad Ishky Rumaf; Achmad Musyahid; La Ode Ismail Ahmad (Pascasarjana UIN Alauddin Makassar, 2023)
The objectives of this research are as follows: 1) To analyze the underlying factors of unregistered marriages in Kecamatan Kota Terante Utara; 2) To analyze the strategies for overcoming unregistered marriages at the office of Religious Affairs in Kecamatan Kota Terante Utara. This research is qualitative research with juridical, sociological, and pedagogical approaches. The data sources for this research are the Religious Affairs Office (KUA) of Kecamatan Kota Ternate Utara and religious figures. The data collection methods used are observation, interviews, documentation, and reference tracing. Data analysis techniques include data categorization, reduction, grouping, arrangement, interpretation, verification, and conclusions. The research results are as follows: The practice of unregistered marriages in Kecamatan Kota Ternate Utara is still common to this day due to several factors, including the economic limitations of the community, low levels of education, a lack of legal knowledge, and an understanding of the importance of marriage registration. The strategies of KUA in addressing unregistered marriages in Terante Utara include providing counseling on marriage registration and family happiness to prospective brides and guardians, as well as promoting the importance of marriage registration and its negative consequences for families, mothers, and children through seminars and prayer sessions organized by the Religious Affairs Committee through representatives of the subunit held within the community.